Higher Rate of Lymphedema with Inguinal versus Axillary Complete Lymph Node Dissection for Melanoma: A Potential Target for Immediate Lymphatic Reconstruction? - Melina Deban; Patrick Vallance; Evan Jost; J. Gregory McKinnon; Claire Temple-Oberle (Current Oncology, 2022)
Background: The present study was conducted to define the lymphedema rate at our institution in patients undergoing axillary (ALND) or inguinal (ILND) lymph node dissection (LND) for melanoma. It aimed to examine risk factors predisposing patients to a higher rate of lymphedema, highlighting which patients could be targeted for immediate lymphatic reconstruction (ILR). Methods: A retrospective chart review was conducted between October 2015 and July 2020 to identify patients who had undergone ALND or ILND for melanoma. The main outcome measures were rates of transient and permanent lymphedema. Univariate and multivariate analyses were performed to assess the relationship between lymphedema rate and factors related to patient characteristics, surgical procedure, pathology findings, and adjuvant treatment. Results: Between October 2015 and July 2020, 66 patients underwent LND for melanoma: 34 patients underwent ALND and 32 patients underwent ILND. At a median follow-up of 29 months, 85.3% (n = 29) of patients having had an ALND did not experience lymphedema, versus 50.0% (n = 16) of ILND (p = 0.0019). The rates of permanent lymphedema for patients having undergone ALND and ILND were 11.8% (n = 4) and 37.5% (n = 12) respectively (p = 0.016, NS). The rate of transient lymphedema was 2.9% (n = 1) for ALND and 12.5% (n = 4) for ILND (p = 0.13, NS). On univariate analysis, the location of LND and wound infection were found to be significant factors for lymphedema. On multivariate analysis, only the location of LND remained a significant predictor, with the inguinal location predisposing to lymphedema. Conclusion: This study highlights the high rate of lymphedema following ILND for melanoma and is a potential target for future patients to be considered for ILR.